Risk factors and long-term course of gastroesophageal reflux disease after peroral endoscopic myotomy: A large-scale multicenter cohort study in Japan - Shiwaku, Hironari; Sato, Hiroki; Shimamura, Yuto; Abe, Hirofumi; Shiota, Junya; Sato, Chiaki; Ominami, Masaki; Sakae, Hiroyuki; Hata, Yoshitaka; Fukuda, Hisashi; Ogawa, Ryo; Nakamura, Jun; Tatsuta, Tetsuya; Ikebuchi, Yuichiro; Yokomichi, Hiroshi; Hasegawa, Suguru; Inoue, Haruhiro (Endoscopy, 2022)
Background Gastroesophageal reflux disease (GERD) and reflux esophagitis remain problems after peroral endoscopic myotomy (POEM). This study aimed to elucidate the risk factors and long-term course of reflux esophagitis and symptomatic GERD after POEM. Methods This multicenter cohort study involved 14 high volume centers. Overall, 2905 patients with achalasia-related esophageal motility disorders treated with POEM were analyzed for reflux esophagitis, severe reflux esophagitis (Los Angeles classification C or D), and symptomatic GERD.Results Reflux esophagitis was diagnosed in 1886 patients (64.9 %). Age ≥ 65 years (risk ratio [RR] 0.85), male sex (RR 1.11), posterior myotomy (RR 1.12), esophageal myotomy > 10 cm (RR 1.12), and gastric myotomy > 2 cm (RR 1.17) were independently associated with reflux esophagitis. Severe reflux esophagitis was diagnosed in 219 patients (7.5 %). Age ≥ 65 years (RR 1.72), previous treatments (RR 2.21), Eckardt score ≥ 7 (RR 0.68), sigmoid-type achalasia (RR 1.40), and esophageal myotomy > 10 cm (RR 1.59) were factors associated with severe reflux esophagitis. Proton pump inhibitors (PPIs) were more effective for reflux esophagitis at 5-year follow-up (P = 0.03) than after 1 year (P = 0.08). Symptomatic GERD was present in 458 patients (15.9 %). Symptom duration ≥ 10 years (RR 1.28), achalasia diagnosis (RR 0.68), integrated relaxation pressure ≥ 26 (RR 0.60), and posterior myotomy (RR 0.80) were associated with symptomatic GERD. The incidence of symptomatic GERD was lower at 5-year follow-up compared with that after 1 year (P = 0.04), particularly in PPI users (P < 0.001).Conclusions The incidence of severe reflux esophagitis was low after POEM, but excessive myotomy for older patients with previous treatments should be avoided. Early phase symptomatic GERD is non-acid reflux dependent and the natural course is favorable, basically supporting conservative treatment.